Barriers and facilitators to consulting hospital clinical ethics committees - Gaudine, Alice (Nursing ethics, 2011)
Hospitals in many countries have had clinical ethics committees for over 20 years. Despite this, there has been little research to evaluate these committees and growing evidence that they are underutilized. To address this gap, we investigated the question ‘What are the barriers and facilitators nurses and physicians perceive in consulting their hospital ethics committee?’ Thirty-four nurses, 10 nurse managers and 31 physicians working at four Canadian hospitals were interviewed using a semi-structured interview guide as part of a larger investigation. We used content analysis of the interview data related to barriers and facilitators to use of hospital ethics committees to identify nine categories of barriers and nine categories of facilitators. These categories as well as their subcategories are discussed and those specific to nurses or physicians are identified. The need to increase health professionals' use of clinical ethics committees through reducing barriers and maximizing facilitators is discussed.